2022
DOI: 10.1002/ese3.1077
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hierarchical optimization method for emergency energy management of microgrids with energy storage systems

Abstract: When failures occur in microgrids (MGs), the energy management for emergencies is required. To respond to emergencies in MGs rapidly, an accelerated hierarchical optimization method has been proposed, where the outputs of energy storage systems (ESSs) are controlled to provide urgent supports, before the MG reconfiguration starts. However, it is time-consuming to find the optimal schemes for MG reconfiguration. To reduce the time of reconfiguration, an optimization method based on deep neural networks (DNNs) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is anticipated that the generation of wind energy using OWFs can be nearly 54 GW in the United States [5]. The technical complexities associated with the implementation of offshore platforms and the process of transferring power from OWF to onshore power grids needs significant attention [6][7][8]. Previous studies have shown that the HVDC transmission is superior to HVAC transmission in terms of improved technical and economic feasibility, sustainability, and flexibility of integration with larger wind farms located at greater distances [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated that the generation of wind energy using OWFs can be nearly 54 GW in the United States [5]. The technical complexities associated with the implementation of offshore platforms and the process of transferring power from OWF to onshore power grids needs significant attention [6][7][8]. Previous studies have shown that the HVDC transmission is superior to HVAC transmission in terms of improved technical and economic feasibility, sustainability, and flexibility of integration with larger wind farms located at greater distances [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, MGs have the potential to facilitate the widespread adoption of renewable energy sources and plug-in electric vehicles (PEVs), therefore alleviating global ecological and climate-change issues. 1,2 In addition to improving power quality and decreasing operational costs, MGs would provide additional benefits to power systems, such as decreasing power losses owing to the close proximity of the load and the generating. It is possible for MGs to operate either in synchrony with the grid or independently of it.…”
Section: Introductionmentioning
confidence: 99%
“…Microgrids (MGs) are characterized as localized power systems that use distributed generation (DG) and active consumers with upstream system connectivity. As a result, MGs have the potential to facilitate the widespread adoption of renewable energy sources and plug‐in electric vehicles (PEVs), therefore alleviating global ecological and climate‐change issues 1,2 . In addition to improving power quality and decreasing operational costs, MGs would provide additional benefits to power systems, such as decreasing power losses owing to the close proximity of the load and the generating.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [1] firstly established a naturally determined and systematic control of multiple decision variables as a robust optimal game for game players. Reference [2] introduced a robust optimal planning algorithm considering wind speed uncertainty.…”
Section: Introductionmentioning
confidence: 99%